#TITLE_ALTERNATIVE# - FIKRIL BASHARAH (NIM 13204047), ABDUH
Analysis of output current and voltage ripple of single-phase PWM full-bridge inverters is proposed in this research. Analysis begins with deriving a general expression for the rms value of output current and voltage harmonic of single-phase PWM inverters as a function of reference signal with five different techniques. Optimum values of LC filter those results in minimum output current and voltage harmonic of single-phase full-bridge PWM inverters can be derived from this general expression. The analysis shows that the rms value of output harmonic in five techniques have different characteristics. For Asymmetrical 1 and 2, harmonic characteristic nearly equal, and also for Symmetrical 1 and 2 have same shape. For bipolar technique, the characteristic is different from four techniques before. Simulation results are also presented to show the validity of the proposed analyzing method.